2017
DOI: 10.1007/s11295-017-1160-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the slow-melting flesh character in peach

Abstract: The slow melting flesh (SMF) trait in peach [Prunus persica (L.) Batsch] defines a slower process of postharvest fruit softening than the prevalent melting flesh (MF) types. This gives a longer shelf-life and a delayed harvest time resulting in better fruit quality. Unlike other known fruit texture traits, SMF is difficult to measure and has a complex inheritance. We examined this character over two years in the offspring of two crosses, both with 'Big Top', a SMF nectarine, as female parent, and a melting fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…The activity of an endo-polygalacturonase gene was associated with M flesh [ 48 ]. Recently, Serra et al [ 49 ] identified the qP-MD5 QTL as a key factor for slow M flesh, and qP-MD6 may modulate the maturity date trait. With the development of sequencing and SNP-genotyping platforms, high-resolution linkage maps have been successfully used to locate qualitative and quantitative traits [ 21 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activity of an endo-polygalacturonase gene was associated with M flesh [ 48 ]. Recently, Serra et al [ 49 ] identified the qP-MD5 QTL as a key factor for slow M flesh, and qP-MD6 may modulate the maturity date trait. With the development of sequencing and SNP-genotyping platforms, high-resolution linkage maps have been successfully used to locate qualitative and quantitative traits [ 21 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of peach, there is an additional advantage: recent results have shown that vast regions of the chromosomes of the modern cultivars (sometimes accounting for 40-60% of the genome) are monomorphic (Donoso et al, 2015;Serra et al, 2017), identity by descent (IBD) being the most logical cause due to a high level of co-ancestry (Micheletti et al, 2015) of peach commercial cultivars. This determines that some of the crossovers produced at the homozygous DNA fragments will not be effective.…”
Section: Genetic Basis Of the Resynthesis Processmentioning
confidence: 99%
“…In the case of peach, there is an additional advantage: recent results have shown that vast regions of the chromosomes of the modern cultivars (sometimes accounting for 40-60% of the genome) are monomorphic (Serra et al 2017, Donoso et al 2015, identity by descent (IBD) being the most logical cause due to a high level of co-ancestry (Micheletti et al 2015) of peach commercial cultivars. This determines that some of the crossovers produced at the homozygous DNA fragments will not be effective.…”
Section: Genetic Basis Of the Resynthesis Processmentioning
confidence: 99%